A novel approach for improving the performance of air engine to achieve zero-emission for a pollution-free environment. (2020) - Aravindhan, N.; Maclin John Vasanth, K.; Vignesh Kumar, R.; Jayasurya, M.; Suriya Prakash, S.; Sabareeshwaran, V.
Abstract: To attain sustainable development in the field of automobile we need new sources to emerge. In which the alternative fuel plays a vital role. Considering the present situation, we have to go for alternative fuel which should low cost and easily available for us. The development of compressed air technology leads to maintain a high level of marketability of new innovative products that extends beyond an environmentally conscious group into mainstream society. The major development of compressed air in automobiles is compressed air cars. Its zero-emission ability provides our advantage over other fuels. The main problem raised over the implementation of the air as a fuel is it expanded freely. In this work, we proposed a novel approach to avoid the freezing of the air inside the piston chamber in order to increase its efficiency.